Libgram assist: An innovative librarianship for the Future /Roziya Abu...[et al] - Abu, Roziya; Jasmin, Ilani Nur Adriani; Wan Omar, Wan Noor Faaizah; Mohd Johari, Muhammad Rafi Izzuan (Universiti Teknologi MARA, Kedah, 2019)
LibGram Assist is a prototype of an arithmetical hologram projection of a librarian in a library environment. Using the latest technology of fairy light, LibGram Assist aim to support the new digital library environment hence, forever change the perception of the society about library, information sharing and information archive. It uses fairy light technology that applies femtosecond lasers to ionize air molecules and thus create crackling, photon-emitting pockets of plasma. These lights, or "voxels," can be arranged in mid-air to create interactive and floating images. Users can touch; feel and control them. LibGram Assist are visualize as a 3D librarian hologram that appear to float in mid-air. LibGram Asst proposed to support a library to manage librarian routines communication tasks in providing library and references services to students and users. The LibGram Assist can be use by students and users (including handicapped users) to inquire and also to obtain information about the library and its resources by providing them the direction to find library material and resources. But most importantly, LibGram support both, 4IR and Malaysia TVET vision. LibGram Asist is a preliminary study done using a quantitative survey on twenty random sampling respondents during the International Innovation & Design in Library & Information Science Competition (InDeLib) 2018. Hence, this paper, discusses the acceptance of users (students and professionals) to the notion of interactive and innovative communication and information sharing using alternative form of artificial intelligence.